A series of dinuclear lanthanide complexes with slow magnetic relaxation for Dy2 and Ho2. Issue 41 (26th September 2016) - Zhang, Jin; Zhang, Haifeng; Chen, Yanmei; Zhang, Xiangfei; Li, Yahong; Liu, Wei; Dong, Yaping
Abstract : Seven dinuclear complexes [Ln2 L2 (C2 H5 OH)2 (NO3 )2 ]·0.5py were prepared and characterized; complex4 exhibits SMM behavior with a U eff value of 66.7 K. Abstract : The employment of a new Schiff base ligand, 2-[(2-hydroxy-3-methoxybenzyl)imino]methylnaphthalen-1-ol (H2 L), in 4f-metal chemistry has led to the formation of seven new isostructural lanthanide(iii ) complexes. More specifically the 1 : 1 reaction of Ln(NO3 )3 ·6H2 O and H2 L in ethanol in the presence of 3 equivalents of pyridine yielded seven dinuclear complexes of compositions [Ln2 L2 (NO3 )2 (C2 H5 OH)2 ]·0.5py (Ln = Eu (1 ), Gd (2 ), Tb (3 ), Dy (4 ), Ho (5 ), Er (6 ), Yb (7 ); py = pyridine). The structures of the isomorphous complexes1–7 were determined by single-crystal X-ray crystallography. X-ray crystallography data reveal that each compound is neutral, and contains two doubly-deprotonated ligands, two chelated nitrates and two coordinated ethanol molecules. The two Ln III atoms in1–7 are doubly bridged by the two phenolato oxygen atoms of two L 2− ligands. Each of the two lanthanide ions is eight-coordinated and possesses distorted dodecahedron geometry. Dc magnetic susceptibility studies in the 2–300 K range reveal probably a weak antiferromagnetic interaction for2, 3 and6, and a ferromagnetic interaction at low temperature for4 and5 . Complexes4 and5 show slow magnetic relaxation behavior. The U eff for4 of 66.7 K is a relatively high value among the reported Dy2 SMMs. Complex5 is a very rare example of a Ho2 compound which exhibits slow magnetic relaxation.